Spherical composite carbon-coated positive electrode lithium supplementing material and preparation method and application thereof

Through solvent thermal method and high-temperature annealing process, spherical composite carbon-coated lithium-ferrate lithium-ferrate materials were prepared, which solved the problems of complex preparation process and poor performance of existing positive electrode lithium-added materials, and achieved efficient and stable positive electrode lithium-added materials.

CN119725542APending Publication Date: 2025-03-28GANFENG LITHIUM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411943545.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing preparation process of the positive electrode lithium supplement material is complex and the resulting material has poor performance, especially in terms of air stability and electrical conductivity.

Method used

The lithium source, iron source, organic composite carbon source, organic solvent and dispersant were mixed and reacted by solvent thermal method to obtain intermediate products, and then subjected to high-temperature annealing to form a spherical composite carbon-coated lithium-rich ferrate material.

Benefits of technology

The spherical composite carbon coated cathode lithium supplement material prepared by this method has better electrochemical properties and air stability, and improves the conductivity of the material and the transfer speed of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725542A_ABST
    Figure CN119725542A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery materials, and provides a spherical composite carbon-coated positive electrode lithium supplementing material and a preparation method and application thereof. The preparation method comprises the following steps: mixing a lithium source, an iron source, an organic composite carbon source, an organic solvent and a dispersing agent, and performing solvothermal reaction to obtain an intermediate product; and performing high-temperature annealing on the intermediate product to obtain the spherical composite carbon-coated anode lithium supplementing material. The preparation process is simple and efficient, and the spherical composite carbon-coated positive electrode lithium supplementing material prepared by the preparation process has a spherical core-shell structure and comprises a lithium-rich lithium ferrite core and a composite carbon-coated layer shell, so that the stability of the positive electrode lithium supplementing material in air and the conductivity of the positive electrode lithium supplementing material are greatly improved, and meanwhile, the stability of the positive electrode lithium supplementing material is greatly improved. The spherical composite carbon-coated positive electrode lithium supplement material also has the characteristics of high purity, controllable morphology and good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a spherical composite carbon-coated positive electrode lithium supplement material and a preparation method and application thereof. Background Art

[0002] During the initial charge and discharge process of a lithium battery, the lithium ions of the positive electrode material migrate to the negative electrode to form a SEI film. The SEI film consumes some lithium ions, causing the initial coulombic efficiency of the lithium battery to decrease, and thus the positive electrode lithium replenishment technology was born.

[0003] Among many lithium supplements, lithium-rich ferrite has superior lithium supplementation effect, simple operation, and broad application prospects, but its air stability is very poor and its electrical conductivity is also poor. When using the traditional high-temperature solid-phase method to prepare lithium-rich ferrite, problems such as coarse particles and uneven mixing during sintering are often encountered; the hydrothermal method faces challenges because lithium-rich ferrite easily reacts with water; although the sol-gel method can better control the material structure, its complex operation process also brings certain difficulties to practical applications. At present, these conventional processes not only have cumbersome preparation processes, but the resulting materials often have poor electrical conductivity and poor stability.

[0004] Therefore, it is of great significance to develop a positive electrode lithium replenishing material with excellent performance and simple preparation process. Summary of the invention

[0005] In view of this, the present invention provides a spherical composite carbon-coated positive electrode lithium supplement material and a preparation method and application thereof, so as to solve the problems that the preparation process of the existing lithium supplement material is complicated and the performance of the prepared lithium supplement material is poor.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a method for preparing a spherical composite carbon-coated positive electrode lithium supplement material, comprising the following steps:

[0008] 1) mixing a lithium source, an iron source, an organic composite carbon source, an organic solvent and a dispersant, and performing a solvothermal reaction to obtain an intermediate product;

[0009] 2) The intermediate product is subjected to high temperature annealing to obtain a spherical composite carbon-coated positive electrode lithium replenishing material.

[0010] Preferably, in step 1), the molar ratio of lithium in the lithium source to iron in the iron source is 4.9-5.5:1; the mass ratio of the organic composite carbon source, organic solvent, dispersant to the total mass of the lithium source and the iron source is 0.15-0.2:5-10:0.01-0.02:1.

[0011] Preferably, the lithium source includes lithium oxalate and / or lithium citrate; the iron source includes ferric oxalate and / or ferric citrate; the organic composite carbon source includes one or more of triethyl aluminum, diisopropyl titanate, ethyl silicate and tetramethyl tin; the organic solvent includes one or more of methanol, ethanol, ethylene glycol and toluene; the dispersant includes one or more of glycerol, stearic acid, polyvinyl pyrrolidone and N-methylpyrrolidone.

[0012] Preferably, the temperature of the solvent thermal reaction in step 1) is 180-300° C., the heating rate is 0.5-2° C. / min, and the time is 10-20 h.

[0013] Preferably, the high temperature annealing in step 2) is performed at a temperature of 600 to 800° C., a heating rate of 5 to 10° C. / min, and a time of 10 to 20 hours.

[0014] The present invention also provides a spherical composite carbon-coated positive electrode lithium replenishing material prepared by the above-mentioned spherical composite carbon-coated positive electrode lithium replenishing material preparation method. The spherical composite carbon-coated positive electrode lithium replenishing material is a spherical core-shell structure, including a lithium-rich lithium ferrite core and a composite carbon coating layer shell.

[0015] Preferably, the particle size of the spherical composite carbon-coated positive electrode lithium supplement material is 1 to 5 μm.

[0016] Preferably, the thickness of the composite carbon coating layer shell is 50-100 nm.

[0017] The present invention also provides an application of the spherical composite carbon-coated positive electrode lithium supplement material in the preparation of a lithium battery.

[0018] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0019] The core of the spherical composite carbon-coated positive electrode lithium replenishing material described in the present invention is lithium-rich lithium ferrite, and the shell is a composite carbon coating layer, wherein the thickness of the composite carbon coating layer is 50 to 100 nm, and the lithium-rich lithium ferrite core is coated to form a positive electrode lithium replenishing material with a spherical microscopic morphology. The spherical morphology can better exert the electrical properties of the positive electrode lithium replenishing material, and the composite carbon coating layer of the shell also makes the positive electrode lithium replenishing material more stable in the air, thereby improving the electrical conductivity of the positive electrode lithium replenishing material.

[0020] The preparation method of the present invention can obtain a spherical composite carbon-coated lithium-rich iron oxide material with adjustable morphology by a solvothermal method. During the preparation process, by adding an organic solvent and reacting in an organic solvent, the iron-lithium distribution is more uniform, the synthesized material has a higher purity, and the particle size of the material is controlled by controlling the heating curve and the concentration of the organic solvent, so that the morphology of the material can be controlled. In addition, by high-temperature annealing of the positive electrode lithium supplement material, the carbon source on the surface of the lithium-rich iron oxide material is further carbonized, and the obtained nanometer-level thickness composite carbon layer not only improves the stability of the positive electrode lithium supplement material in the air, but also improves the conductivity of the positive electrode lithium supplement material and the transfer speed of lithium ions. In summary, the preparation process of the positive electrode lithium supplement material of the present invention is not only simple and efficient, but also the obtained product has high purity, controllable morphology, good electrochemical performance, and excellent stability in the air, which opens up a new path for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0022] Figure 1 This is the XRD pattern of the spherical aluminum composite carbon coated positive electrode lithium supplement material prepared in Example 1;

[0023] Figure 2 This is the SEM image of the spherical aluminum composite carbon coated positive electrode lithium replenishing material prepared in Example 1. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a spherical composite carbon-coated positive electrode lithium supplement material, comprising the following steps:

[0025] 1) mixing a lithium source, an iron source, an organic composite carbon source, an organic solvent and a dispersant, and performing a solvothermal reaction to obtain an intermediate product;

[0026] 2) The intermediate product is subjected to high temperature annealing to obtain a spherical composite carbon-coated positive electrode lithium replenishing material.

[0027] In the present invention, the molar ratio of lithium in the lithium source to iron in the iron source in step 1) is 4.9-5.5:1, preferably 5.0-5.3:1, and more preferably 5.1:1; the mass ratio of the organic composite carbon source, the organic solvent, the dispersant to the total mass of the lithium source and the iron source is 0.15-0.2:5-10:0.01-0.02:1, preferably 0.165-0.19:5.5-8.5:0.012-0.018:1, further preferably 0.17-0.185:6-8:0.013-0.016:1, and more preferably 0.18:7.5:0.015:1.

[0028] In the present invention, the lithium source includes lithium oxalate and / or lithium citrate, preferably lithium citrate; the iron source includes ferric oxalate and / or ferric citrate, preferably ferric citrate; the organic composite carbon source includes one or more of triethylaluminum, diisopropyl titanate, ethyl silicate and tetramethyltin, preferably triethylaluminum; the organic solvent includes one or more of methanol, ethanol, ethylene glycol and toluene, preferably methanol; the dispersant includes one or more of glycerol, stearic acid, polyvinyl pyrrolidone and N-methylpyrrolidone, preferably glycerol.

[0029] In the present invention, the order of mixing in step 1) is preferably to first dissolve the lithium source and the iron source in the organic solvent, and then add the organic composite carbon source and the dispersant.

[0030] In the present invention, the solvothermal reaction in step 1) also includes an ultrasonic dispersion operation, and the ultrasonic dispersion operation is preferably to pour a mixture obtained by mixing a lithium source, an iron source, an organic composite carbon source, an organic solvent and a dispersant into a polytetrafluoroethylene liner of a reaction kettle, and then place the reaction kettle in an ultrasonic disperser for ultrasonic dispersion.

[0031] In the present invention, the frequency of the ultrasonic dispersion is preferably 20 to 30 KHz, more preferably 22 to 28 KHz, and more preferably 23 to 25 KHz; the time of ultrasonic dispersion is preferably 0.5 to 2 h, more preferably 0.8 to 1.6 h, and more preferably 1 to 1.2 h.

[0032] In the present invention, the temperature of the solvothermal reaction in step 1) is 180-300°C, preferably 200-280°C, more preferably 220-275°C, and more preferably 250-260°C; the heating rate of the solvothermal reaction is 0.5-2°C / min, preferably 0.6-1.7°C / min, more preferably 0.8-1.5°C / min, and more preferably 1-1.3°C / min; the time of the solvothermal reaction is 10-20h, preferably 11-18h, more preferably 12.5-16h, and more preferably 13-15h.

[0033] In the present invention, the temperature of the high temperature annealing in step 2) is 600-800°C, preferably 620-780°C, more preferably 650-750°C, and more preferably 700°C; the heating rate of the high temperature annealing is 5-10°C / min, preferably 5.5-8°C / min, more preferably 6-7.5°C / min, and more preferably 6.5°C / min; the time of the high temperature annealing is 10-20h, preferably 12-18h, more preferably 12.5-16h, and more preferably 15h.

[0034] The present invention also provides a spherical composite carbon-coated positive electrode lithium replenishing material prepared by the above-mentioned spherical composite carbon-coated positive electrode lithium replenishing material preparation method. The spherical composite carbon-coated positive electrode lithium replenishing material is a spherical core-shell structure, including a lithium-rich lithium ferrite core and a composite carbon coating layer shell.

[0035] In the present invention, the particle size of the spherical composite carbon-coated positive electrode lithium supplement material is 1 to 5 μm, preferably one of 1 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, and 5 μm, and more preferably 2 μm.

[0036] In the present invention, the chemical formula of the lithium iron oxide-rich lithium core is Li5FeO4.

[0037] In the present invention, the thickness of the outer shell of the composite carbon coating layer is 50 to 100 nm, preferably 55 to 90 nm, more preferably 60 to 85 nm, and more preferably 65 to 70 nm.

[0038] In the present invention, the outer shell of the composite carbon coating layer contains one or more of Al, Si, Ti and Sn, and the doping of these metals can improve the electrical conductivity of the material.

[0039] The present invention also provides an application of the spherical composite carbon-coated positive electrode lithium supplement material in the preparation of a lithium battery.

[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0041] Example 1

[0042] 10.5 g of lithium citrate and 7.35 g of ferric citrate (the molar ratio of lithium to iron is 5:1) are dissolved in 80 g of methanol, and 0.12 g of glycerol and 3 g of triethylaluminum are added to obtain a mixture; the mixture is poured into the polytetrafluoroethylene liner of the reactor, and the reactor is placed in an ultrasonic disperser. After ultrasonic dispersion at a frequency of 20 kHz for 1 hour, the reactor is placed in a high-temperature furnace, heated to 275°C at a heating rate of 1°C / min, and kept warm for 10 hours for a solvent thermal reaction. The solid product obtained after the solvent thermal reaction is then transferred to a tubular furnace, heated to 800°C at a heating rate of 5°C / min, and kept warm for 15 hours for high-temperature annealing. Finally, a spherical aluminum composite carbon-coated positive electrode lithium supplement material with a particle size of 2 μm is obtained after cooling (referred to as material 1), wherein the thickness of the composite carbon coating layer shell is 50 nm.

[0043] The XRD and SEM images of the spherical aluminum composite carbon coated positive electrode lithium supplement material prepared in Example 1 are shown in Figures 1 and 2. Figure 1 and Figure 2 As shown, from Figure 1 It can be seen from the XRD diagram that the spherical aluminum composite carbon-coated positive electrode lithium supplement material prepared in this embodiment has no impurity peaks and high purity; Figure 2 It can be seen from the SEM image that the microscopic morphology of the spherical aluminum composite carbon-coated positive electrode lithium supplement material prepared in this embodiment is spherical, and the surface is evenly coated with a carbon layer.

[0044] Example 2

[0045] 10.5g of lithium citrate and 7.35g of ferric citrate (the molar ratio of lithium to iron is 5:1) are dissolved in 130g of methanol, and 0.15g of glycerol and 4g of diisopropyl titanate are added to obtain a mixture; the mixture is poured into the polytetrafluoroethylene liner of the reactor, and the reactor is placed in an ultrasonic disperser. After ultrasonic dispersion at a frequency of 20KHz for 1h, the reactor is placed in a high-temperature furnace, heated to 300℃ at a heating rate of 1℃ / min, and kept warm for 10h for solvent thermal reaction, and then the solid product obtained after the solvent thermal reaction is transferred to a tubular furnace, heated to 700℃ at a heating rate of 10℃ / min, and kept warm for 10h for high-temperature annealing, and finally cooled to obtain a spherical titanium composite carbon-coated positive electrode lithium supplement material with a particle size of 1μm, wherein the thickness of the composite carbon coating layer shell is 20nm.

[0046] Example 3

[0047] 10.5g of lithium citrate and 7.35g of ferric citrate (the molar ratio of lithium to iron is 5:1) are dissolved in 100g of methanol, and 0.15g of glycerol and 3g of ethyl silicate are added to obtain a mixture; the mixture is poured into the polytetrafluoroethylene liner of the reactor, and the reactor is placed in an ultrasonic disperser. After ultrasonic dispersion at a frequency of 20KHz for 2h, the reactor is placed in a high-temperature furnace, heated to 200℃ at a heating rate of 1℃ / min, and kept warm for 10h for solvent thermal reaction, and then the solid product obtained after the solvent thermal reaction is transferred to a tubular furnace, heated to 700℃ at a heating rate of 5℃ / min, and kept warm for 15h for high-temperature annealing, and finally cooled to obtain a spherical silicon composite carbon-coated positive electrode lithium supplement material with a particle size of 3μm, wherein the thickness of the composite carbon coating layer shell is 50nm.

[0048] Example 4

[0049] 5.10g of lithium oxalate and 3.76g of ferric oxalate (the molar ratio of lithium to iron is 5:1) are dissolved in 60g of ethylene glycol, and 0.05g of polyvinyl pyrrolidone and 2g of triethylaluminum are added to obtain a mixture; the mixture is poured into the polytetrafluoroethylene liner of the reactor, and the reactor is placed in an ultrasonic disperser. After ultrasonic dispersion at a frequency of 20KHz for 2h, the reactor is placed in a high-temperature furnace, heated to 180°C at a heating rate of 1°C / min, and kept warm for 12h for a solvent thermal reaction. The solid product obtained after the solvent thermal reaction is then transferred to a tubular furnace, heated to 750°C at a heating rate of 5°C / min, and kept warm for 12h for high-temperature annealing. Finally, a spherical silicon composite carbon-coated positive electrode lithium supplement material with a particle size of 5μm is obtained after cooling, wherein the thickness of the composite carbon coating layer shell is 100nm.

[0050] Example 5

[0051] 5.10g of lithium oxalate and 3.76g of ferric oxalate (the molar ratio of lithium to iron is 5:1) are dissolved in 80g of toluene, and 0.1g of polyvinyl pyrrolidone and 2g of diisopropyl titanate are added to obtain a mixture; the mixture is poured into the polytetrafluoroethylene liner of the reactor, and the reactor is placed in an ultrasonic disperser. After ultrasonic dispersion at a frequency of 20KHz for 2h, the reactor is placed in a high-temperature furnace, heated to 210°C at a heating rate of 1°C / min, and kept warm for 15h for a solvent thermal reaction. The solid product obtained after the solvent thermal reaction is then transferred to a tubular furnace, heated to 800°C at a heating rate of 10°C / min, and kept warm for 12h for high-temperature annealing. Finally, a spherical silicon composite carbon-coated positive electrode lithium supplement material with a particle size of 5μm is obtained after cooling, wherein the thickness of the composite carbon coating layer shell is 100nm.

[0052] Experimental Example 1

[0053] Three groups of materials 1 prepared in Example 1 were taken, and after being exposed to air for 0 h, 12 h and 24 h respectively, the three groups of materials 1 were weighed and slurried with conductive carbon (conductive graphite KS-6) and PVDF at a mass ratio of 8:1:1 to obtain slurries, and then the slurries were coated on aluminum foil, dried, rolled, cut and assembled into button batteries; then the electrical performance of the button batteries coated with material 1 was tested. The experimental results are shown in Table 1.

[0054] Table 1 Electrical performance test results

[0055]

[0056] It can be seen from Table 1 that after the spherical silicon composite carbon coated positive electrode lithium replenishing material of the present invention is exposed to the air, it has little effect on the capacity of the battery, indicating that the positive electrode lithium replenishing material prepared by the present invention has good stability in the air and has good electrical properties and conductivity properties.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a spherical composite carbon-coated positive electrode lithium supplement material, characterized in that: The steps include: 1) mixing a lithium source, an iron source, an organic composite carbon source, an organic solvent and a dispersant, and performing a solvothermal reaction to obtain an intermediate product; 2) The intermediate product is subjected to high temperature annealing to obtain a spherical composite carbon-coated positive electrode lithium replenishing material.

2. The method for preparing a spherical composite carbon-coated positive electrode lithium supplement material according to claim 1, characterized in that: The molar ratio of lithium in the lithium source to iron in the iron source in step 1) is 4.9-5.5:1; The mass ratio of the organic composite carbon source, the organic solvent, the dispersant to the total mass of the lithium source and the iron source is 0.15-0.2:5-10:0.01-0.02:

1.

3. The method for preparing a spherical composite carbon-coated positive electrode lithium supplement material according to claim 2, characterized in that: The lithium source includes lithium oxalate and / or lithium citrate; The iron source includes ferric oxalate and / or ferric citrate; The organic composite carbon source includes one or more of triethylaluminum, diisopropyl titanate, ethyl silicate and tetramethyl tin; The organic solvent includes one or more of methanol, ethanol, ethylene glycol and toluene; The dispersant includes one or more of glycerol, stearic acid, polyvinyl pyrrolidone and N-methyl pyrrolidone.

4. The method for preparing a spherical composite carbon-coated positive electrode lithium supplement material according to any one of claims 1 to 3, characterized in that: The temperature of the solvent thermal reaction in step 1) is 180-300° C., the heating rate is 0.5-2° C. / min, and the time is 10-20 h.

5. The method for preparing a spherical composite carbon-coated positive electrode lithium supplement material according to claim 4, characterized in that: The high temperature annealing in step 2) is performed at a temperature of 600 to 800° C., a heating rate of 5 to 10° C. / min, and a time of 10 to 20 hours.

6. The spherical composite carbon-coated positive electrode lithium-replenishing material prepared by the method for preparing the spherical composite carbon-coated positive electrode lithium-replenishing material according to any one of claims 1 to 5, characterized in that: The spherical composite carbon-coated positive electrode lithium supplement material is a spherical core-shell structure, comprising a lithium-rich lithium ferrite core and a composite carbon coating layer shell.

7. The spherical composite carbon-coated positive electrode lithium supplement material according to claim 6, characterized in that: The particle size of the spherical composite carbon-coated positive electrode lithium supplement material is 1 to 5 μm.

8. The spherical composite carbon-coated positive electrode lithium supplement material according to claim 7, characterized in that: The thickness of the composite carbon coating layer shell is 50-100 nm.

9. Use of the spherical composite carbon-coated positive electrode lithium supplement material according to any one of claims 6 to 8 in the preparation of lithium batteries.

Citation Information

Cited By

  • Composite lithium supplement agent and preparation method and application thereof

    CN121617970A